Regulations for broadcast media on Islamic values and Afghanistan's national interests - Noor Anwar Farooqi,; Mahyuddin Daud,; Mohammad Naqib Eishan Jan, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This study analyzes the issue of media content regulation in Afghanistan within Islamic values and national interests. This paper analyzes how media in Afghanistan is restricted or regulated based on religious and national values, and what this process means from a sharia and legal perspective. The main objective of the study is to examine how media policies in Afghanistan are based on religious standards, cultural values, and national unity, and how these regulations can be harmonized with the objectives of Sharia. Employing a doctrinal and qualitative methodology, the paper draws on Islamic values, Afghan legal documents, books, journal papers, and expert opinions. This study attempts to bridge the legal gap and ambiguity in regulating broadcasting in light of Islamic values and national interests. The findings show that regulating broadcasting is considered important for strengthening Islamic values and protecting national unity, but if there is no clear and balanced policy for broadcasting, it will harm the independence of journalism and the free flow of information. The article suggests that in light of the objectives of Sharia, a legal framework is needed that both protects religious values and provides an environment for responsible media activity. The results of this study can help formulate policies that combine the objectives of Sharia, the need for national unity, and international journalism rules.